(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
For many years now the Antimafia movement has been one of the most significant forms of collective movement in Italy. It is a coherent and lasting social movement, perhaps one of the largest in Europe, but it is struggling to find its place in academic studies. This article reviews its fundamental phases and protagonists, underlining the extraordinary role historically played by women and new generations and especially analysing the forms of female contribution.